Morphological based mechanism for adsorption of Hg from natural gas using solid supported ionic liquids - Abbas, T. (Government Institutes Inc., 2014)
Solid supported ionic liquids (SSIL) is a promising, eco-friendly technique to remove mercury from natural gas stream with high efficiency and causing no deteriorating impact on gas processing plant. The mechanism of mercury adsorption based on morphological study using SSIL was studied. BmimCl and KMnO4 were successfully immobilized on activated carbon to adsorb mercury from gas stream. The carbon coated with BmimCl and KMnO4 showed promising ability to capture Hg from gas stream. The capacity of Hg removal was 6.8 mg/g of adsorbent in 72 hr (gas flow rate and mercury vapor concentration were 60 mL/min and 15ppm). A change in surface morphology was noticed due to the formation of Hg complex with BmimCl i-e HgCl2. This is an abstract of a paper presented at the International Gas Union Research Conference (IGRC 2014) (Copenhagen, Denmark 9/17-19/2014).